1994
DOI: 10.1063/1.468408
|View full text |Cite
|
Sign up to set email alerts
|

Alignment of photoions far from threshold

Abstract: We present results of measurements and calculations of the alignment for CO+(B 2Σ+) photoions over an extended energy range (0≤Ek≤210 eV). The polarization of CO+(B 2Σ+→X 2Σ+) fluorescence indicates that the photoions retain significant alignment even at high energies. Agreement between the measured and calculated polarization of the fluorescence is excellent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…9,22 The data are not corrected for differences in rotational alignments. While it is possible to include alignment effects in the present treatment, both theory and experiment demonstrate that the influence is very slight, [81][82][83][84][85] especially at the higher energies employed in the current study. 84,85 The alignment provides a useful complementary probe, particularly for the high energy region, and is the topic of related fluorescence polarization studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…9,22 The data are not corrected for differences in rotational alignments. While it is possible to include alignment effects in the present treatment, both theory and experiment demonstrate that the influence is very slight, [81][82][83][84][85] especially at the higher energies employed in the current study. 84,85 The alignment provides a useful complementary probe, particularly for the high energy region, and is the topic of related fluorescence polarization studies.…”
Section: Resultsmentioning
confidence: 99%
“…84,85 The alignment provides a useful complementary probe, particularly for the high energy region, and is the topic of related fluorescence polarization studies. 84,85 In a simplistic view, Fig. 5 shows that the ions are becoming ''hotter'' with increasing photon energy.…”
Section: Resultsmentioning
confidence: 99%
“…The current study focuses on vibrational branching ratios for these systems where differences in vibrational behavior are also seen to extend far into their respective ionization continua. This study-in conjunction with previous rotational 1,2 and polarization studies 3,4 -demonstrate that molecular aspects of ionization dynamics emerge even far from threshold, and that different molecular motions probe different aspects of the photoionization process.…”
Section: Introductionmentioning
confidence: 55%
“…For example, the rotational distributions for CO were relatively flat in the lower energy region 1,2,30 ͑i.e., 20рh р50 eV) while the vibrational distributions vary significantly in this same region. Similarly, polarization data for CO 3,4 in the high energy region demonstrated that the photoelectron is ejected preferentially along the molecular axis, while the vibrational and rotational data were insensitive to this aspect of the photoelectron ejection. These observations underscore the point that measurements which emphasize molecular aspects elucidate details of the photoelectron scattering dynamics that would be otherwise inaccessible.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation